Effect of remote ischemic postconditioning on hepatic ischemia–reperfusion injury in patients undergoing laparoscopic hepatectomy: a randomized double-blinded controlled trial - Yang, Chao; Yang, Lijun; Zeng, Mingwang; Zhu, Yunyan; Zhang, Chuanwu; Chen, Jing; Wang, Yi; Peng, Jinji; Wang, Li-feng; Zhong, Maolin; Xie, Haiyu; Liang, Weidong (Frontiers in Medicine, 2025)
BackgroundHepatic ischemia–reperfusion injury (HIRI) remains a major determinant of outcomes after hepatectomy with hepatic portal occlusion. Animal studies suggest that remote ischemic postconditioning (RIPostC) could alleviate HIRI, but its clinical value is unclear. This trial aimed to evaluate the efficacy of RIPostC in patients undergoing laparoscopic hepatectomy.MethodsIn this randomized controlled trial, 83 patients were assigned to receive either RIPostC (4 cycles of 5 min ischemia/5 min reperfusion) or no intervention. The primary endpoints were postoperative liver function biochemical markers in the serum [alanine aminotransferase (ALT), aspartate aminotransferase (AST), and total bilirubin (TBIL) levels] on postoperative days 1 and 2. The secondary outcomes included intraoperative variables and hospital stay.ResultsData from a total of 72 patients (36 per group) were analyzed. RIPostC did not significantly reduce ALT, AST or TBIL compared with control group (all p > 0.05). No differences were observed in Pringle time, operation time or length of postoperative hospital stay (p > 0.05).ConclusionThis study represents one of the first randomized controlled clinical evaluations of RIPostC during laparoscopic hepatectomy. Contrary to experimental findings, a single RIPostC protocol did not improve early postoperative liver function.